The Use of FMEA to Analyze Electronic Medical Records to Reduce the Risk of Failure at Rizani Hospital - Nur Rosyidah Hani; Purwadi Purwadhi; Kahar Mulyani (Journal of Economics and Social Sciences (JESS), 2026)
This study aims to identify the potential risk of failure (failure mode), causes, and impact of failure in the implementation of RME at Rizani Paiton Hospital, assess the level of risk priority using the Risk Priority Number (RPN), and formulate recommendations for preventive measures and improvement plans based on the Failure Mode and Effect Analysis (FMEA) method. This study uses a qualitative descriptive approach with a case study design, conducted at Rizani Paiton Hospital in July–November 2025 with purposively selected participants from management elements, SIMRS/IT teams, medical records, nurses, and doctors who are directly involved in the implementation of RME. Data was collected through semi-structured interviews, RME workflow observations, and FMEA form filling, then analyzed through failure mode identification, severity, occurrence, and detection score assessment, and RPN calculation to determine risk priority. The results of the study show that there are several groups of potential major failure risks, including system and network disruptions that hinder access and storage of data, input errors and incompleteness of RME filling by users, limitations of system features and integration, and the risk of data loss and unavailability when needed in clinical services. A number of failure modes have high RPN values so they are categorized as priority risks, especially those that have an impact on service delays, potential clinical errors, and disruptions in the continuity of patient information. The resulting recommendations include strengthening infrastructure and system backup, improving RME features and integration according to service flows, improving user training and assistance, strengthening control and monitoring of documentation completeness, as well as drafting more comprehensive SOPs and RME risk management governance.